Effects of crop load on tree water use in apple (Malus x domestica Borkh.) - Lakatos, T.; Bubán, T. (International Journal of Horticultural Science, 2003)
Sap flow rate measurements were carried out during two consecutive (’on’ and ’off’) years in an apple orchard cv. ’Florina’ M.26 to analyse the effects of various crop load on tree water use. Sap flow rate was measured by thermal dissipation method in trunks of nine trees from June to the harvest. Crop load was between 0.2-9.0 fruits • cm -2 of trunk cross section area (equal to 0.5-35.0 fruits•m-2 of leaf area), trunk diameter varied between 4.7-8.7 cm. Total leaf area was estimated by leaf counting or using shoot girth and leaf area relationship. In both years, fruit growth rate was determined by measuring diameter of 280 marked fruits with 7 days frequency. Fruit volume calculated as a function of fruit diameter based on a previously determined relationship. Total leaf area of trees ranged from 4.4 to 19.5 m2 and it was closely related to trunk cross section area. At high crop load the fruit growth rate peaked in August with 0.51.tree-l.day-1 and the leaf area specific total fruit volume reached 61 m2 before the harvest. There was a linear relationship between total leaf area and daily water use, while the leaf area specific water use was influenced by crop load rate. The relationship was described by piecewise linear regression with the breakpoint at crop load rate of 12 fruits•m2 of leaf area. At low crop load the slope of the fitted regression line was less than at high crop load rate.